2017
DOI: 10.1590/1807-1929/agriambi.v21n3p169-174
|View full text |Cite
|
Sign up to set email alerts
|

Stalk yield of sugarcane cultivars under different water regimes by subsurface drip irrigation

Abstract: This study aimed to evaluate the stalk yield of ten sugarcane cultivars (RB962962, RB931011, RB931530, RB98710, RB92579, RB867515, RB863129, SP791011, RB72545 and VAT90212) subjected to water deficit, full irrigation and water surplus by subsurface drip irrigation, during three cropping seasons (2011-2014). The experiment was conducted at the Experimental Field of Embrapa Meio-Norte, Teresina, Piauí State, Brazil, in dystrophic Red Yellow Argisol. The cultivars RB962962 (162.3 Mg ha-1) and RB867515 (158.5 Mg h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Analysis of the agronomic trait SN of the cultivars in the experiment showed an increment of stalks for the cultivars SP79-1011 (51.13) and SP81-3250 (51.06) (TABLE 5). According to Oliveira et al (2007) and Andrade-Junior et al (2017), this may be due to the genetic characteristics of each variety and to results of edaphoclimatic conditions favorable to the interaction genotype versus environment, promoting higher performance of these genotypes. The lower NS of the cultivars RB867515, SP80-1842 and SP89-1115 could be also due to the influence of the herbicides, because even if they have not showed a significant effect, these cultivars may have had a physiologic disturb when submitted to the active ingredient reducing tillering, same results found by Procópio et al (2015) in their studies.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the agronomic trait SN of the cultivars in the experiment showed an increment of stalks for the cultivars SP79-1011 (51.13) and SP81-3250 (51.06) (TABLE 5). According to Oliveira et al (2007) and Andrade-Junior et al (2017), this may be due to the genetic characteristics of each variety and to results of edaphoclimatic conditions favorable to the interaction genotype versus environment, promoting higher performance of these genotypes. The lower NS of the cultivars RB867515, SP80-1842 and SP89-1115 could be also due to the influence of the herbicides, because even if they have not showed a significant effect, these cultivars may have had a physiologic disturb when submitted to the active ingredient reducing tillering, same results found by Procópio et al (2015) in their studies.…”
Section: Resultsmentioning
confidence: 99%
“…The use of drip irrigation can produce more giant sugarcane stalks and reduce the potential for water loss better than other watering techniques. The use of this drip irrigation system has the potential to be applied to oil palm nurseries because watering with drip irrigation can also reduce the amount of water that comes out with nutrients when watering plants in polybags [7].…”
Section: Introductionmentioning
confidence: 99%
“…There is little published information on the growth, development and yield of sugarcane under high input conditions in these areas. Two experiments for assessing sugarcane yield under irrigation, carried out by Andrade Junior et al (2017) and Andrade Júnior et al (2012) in the state of Piauí (∼4 to 5°S), showed that high yields can be achieved in these regions.…”
Section: Introductionmentioning
confidence: 99%